Molecular Docking - Vlachakis, Dimitrios P. (IntechOpen, 2018)
Molecular docking has always been and will be on the forefront of developments in the eminent field of drug design and medicinal chemistry. At the early days, drug discovery was based on blackboard drawings and expert intuition. However, as times move on, the amount of available information and overall knowledge base that needs to be analyzed cannot be processed manually. This, coupled by the rapid growth in computational infrastructure and processing power, has allowed for the efficient use of molecular docking tools and algorithms to be considered in the greater field of drug discovery. In the postgenomic era, molecular docking has become the key player for the screening of hundreds of thousands of compounds against a repertoire of pharmacological targets.